Fitase na alimentação de frangos de corte - Mariana Masseo Saldanha (2015)
Two experiments were conducted to evaluate the effects of phytase inclusion, with normal and reduced levels of phosphorus, in diets for Cobb® broiler on performance (initial weight, feed intake, weight, weight gain, feed conversion and viability) and broiler bone quality (bone mineral content, bine area, bone mineral density, Seedor index, bone breaking strength, bone resilience, bone stiffness, bone ash and phosphorus percent in tibia). Performance was evaluated in a period from one to 35 days of age of broilers, and bone quality was evaluated at 21 and 35 days of age. The experimental designs were completely randomized with four treatments and six replicates for each experiment. The treatments of the first study were: A Control: 0,45% Pd (initial)/0,40%Pd (growth), without phytase; B 0,45% Pd (initial)/0,40% Pd (growth) + Finase considering recovery; C 0,45% Pd (initial)/0,40% Pd (growth) + Hostazym considering recovery; D negative control: 0,45% Pd (initial)/0,40% Pd (growth) without phytase, considering recovery. The treatments of the second study were: E- Control: 0,35% Pd (initial)/0,30% Pd (growth), without phytase; F- 0,35% Pd (initial)/0,30% Pd (growth) + Finase® considering recovery; G- 0,35% Pd (initial)/0,30% Pd (growth) + Hostazym® considering recovery; H- negative control: 0,35% Pd (initial)/0,30% Pd (growth) without phytase, considering recovery. In the first trial, the use of 0,35% de Pd in the initial phase and 0,30% in the growth phase, without the inclusion of phytase (negative control), resulted in a decreased performance and bone quality of broilers. Furthermore, the enzyme Finase appeared to be more efficient, with similar results to control treatment during the entire rearing period. In the second study, the use of 0,25% Pd in the initial phase and 0,20% in the growth phase, without inclusion of phytase (negative control) resulted in a decreased performance and bone quality of broilers. As in the first study, the Finase enzyme appeared to be more efficient, with similar results to control treatment during de entire rearing period.